Factors Affecting Non-Government Organisations’ Financial Statement Fraud in South Africa: New Fraud Combined Theory Approach - Jean Damascene Mvunabandi; Bomi Cyril Nomlala (Journal of Economics, Business, and Accountancy Ventura, 2022)
This article aims to obtain empirical evidence about the relationship between New Fraud Combined Theory with non-government organizations’ financial statement fraud in South Africa. The population of this thesis research comprised 87 staff from 30 chosen Non-Government organizations (NGOs). The sample size of 87 was calculated using Raosft Software. A convenience sampling technique was used to select the study’s respondents. This article adopted quantitative and descriptive survey research. A Likert questionnaire was designed and used as the research instrument for generating data from respondents. Robustness analysis was entirely performed using descriptive statistics. The result of this research indicated that all variables have a significant association with fraudulent financial statements among NGOs in the eThekwini region, South Africa. This article contributes to the body of knowledge: the significant association between auditing and financial statement fraud mitigation accentuates the new fraud combined theory which belies that effective corporate governance will significantly curb financial statement fraud among NGOs in the eThekwini region and beyond.